OPPORTUNITIES TO DEVELOP THE PROFESSIONAL POTENTIAL OF FUTURE FOREIGN LANGUAGE TEACHERS - Rahmonova, Saodat (Журнал иностранных языков и лингвистики, 2023)
This article is devoted to the emergence of a state of self-reflection (reflexive position) in foreign language teaching in the process of professional education of future foreign language teachers.